1970
DOI: 10.1111/j.1432-1033.1970.tb00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Catechol 1,2‐Oxygenase from Trichosporon cutaneum

Abstract: A highly purified preparation of catechol 1,2-oxygenase was obtained from a strain of Trichosporon cutaneum, isolated from soil as a predominant phenol utilizing yeast. The purified active enzyme was homogeneous upon polyacrylamide gel electrophoresis. The enzyme was gradually inactivated upon storage. The inactivation was followed by the appearance of a second, electrophoretically distinct band. The active enzyme is red, the inactive form is colourless. Its molecular weight is 109000 as determined by gel filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…Enzyme purijication 100 c I Phenol hydroxylase was isolated from T. cutaneum, grown in 800-1 cultures in the medium described before [13]. The cell paste was stored at -70°C.…”
Section: Chemicals and Equipmentmentioning
confidence: 99%
“…Enzyme purijication 100 c I Phenol hydroxylase was isolated from T. cutaneum, grown in 800-1 cultures in the medium described before [13]. The cell paste was stored at -70°C.…”
Section: Chemicals and Equipmentmentioning
confidence: 99%
“…It also occurs with a second enzyme of the phenol degradative pathway, viz. catechol 1,2-oxygenase, for which Km at pH 8.3 is 3.3/zM in situ, but 5.9/zM in vitro [14]. The difference between phenol hydroxylase in situ and the enzyme in vitro extends to energetics of the reaction, the activation enthalpies for phenol hydroxylase in situ being about 75-8007o of those in vitro (table 1).…”
Section: Discussionmentioning
confidence: 94%
“…The purified enzyme exhibited higher activities towards 4-methylcatechol (186%) and hydroxyquinol (159%) than towards catechol (100%), 3-methylcatechol (6%) and pyrogallol (9%), and it was obviously different in the substrate specificity from those isolated from Brevibacterium 5 ) and Trichosporon cutaneum. 6 ) All of the catechol 1,2-oxygenases so far purified and characterized contained nonheme iron as a sole cofactor. 19 ) The enzyme activity was inhibited 53% with KCN (1 mM), which might suggest that the enzyme, differently from other ring-cleaving oxygenases, is a heme iron protein.…”
Section: Discussionmentioning
confidence: 99%
“…6 ) In a previous paper, 7) we reported that catechol 1,2-oxygenase from Trichosporon cutaneum WY 2-2, which isolated by us from an activated sludge, was apparently different in its substrate specificity from the enzyme from T. cutaneum isolated by Neujahr et al 6 ) and the other such enzyme in bacteria.l~5)…”
mentioning
confidence: 81%